ChemInform Abstract: Synthesis of Unsymmetrical NCN′ and PCN Pincer Palladacycles and Their Catalytic Evaluation Compared with a Related SCN Pincer Palladacycle. Issue 48 (10th November 2016) - Roffe, Gavin W.; Tizzard, Graham J.; Coles, Simon J.; Cox, Hazel; Spencer, John
Abstract: Newly developed unsymmetrical palladacycle catalysts are tested in an aldol condensation reaction as well as in a vinyl epoxide coupling.